Acceptance Analysis of The East Java Province E-Procurement System Using TAM Method - Mas Odi; Erma Suryani (IPTEK The Journal for Technology and Science, 2020)
Technological developments have changed the system of the government. The EastJava Provincial Government utilizes Information and Communication Technologyfor the procurement of goods and services. This study aims to measure the level ofacceptance of technology in the system and the satisfaction of applications for thegoods and services procurement in East Java Province. The results of this study canbe used to improve the system that has been made. This study uses the TechnologyAcceptance Model (TAM) method in measuring using (5) aspects, namely Perceptionof Ease of Use, Benefits of Use, Attitudes toward behavior, Interest in Behavior, andBehavior. This study used 90 respondents. The results showed that from the regres-sion test on the variable Perception of Ease of Use with Benefits of Use of 13.5%,Perception of Ease of Use with Attitudes Against Behavior amounted to 38.7%. Ben-efits of Using Attitudes Against Behavior was 23.9%, Benefits of Use with InterestBehavior amounted to 11.5%, Attitudes toward Behavior were Large with Interest inBehavior at 22.2%. Benefits of Use with Behavior amounted to 10.1%, and Interestsin Behavior with Behavior were 13.2%. The study results show that the user’s easeand attitude have the highest value and interest in behavior. Therefore the East Javaprovincial government can maintain the procurement application.